2017
DOI: 10.1177/1471301217712796
|View full text |Cite
|
Sign up to set email alerts
|

Day Care for People with Dementia: A Qualitative Study Comparing Experiences from Norway and Scotland

Abstract: Potential benefits from day care attendance are reported in the literature for both people with dementia and caregivers, although the evidence-base is limited. The study aimed to explore and compare experiences of day care services for people with dementia as described by day care attendees and their caregivers in Norway and Scotland. Whereas day care receives prominence in Norway's national plan, Scotland does not highlight day care in its national dementia strategy. A qualitative cross-national comparative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…This is in accordance with other studies describing the meaning of the social interaction that is taking place during a meal. 9 , 24 , 45 In a systematic meta-synthesis from 2016, Eriksen et al found that it is of importance for people with dementia to meet others in the same situation to feel equality, comfort, and safety. 46 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with other studies describing the meaning of the social interaction that is taking place during a meal. 9 , 24 , 45 In a systematic meta-synthesis from 2016, Eriksen et al found that it is of importance for people with dementia to meet others in the same situation to feel equality, comfort, and safety. 46 …”
Section: Discussionmentioning
confidence: 99%
“…4 These services should also serve as a respite for family caregivers, and it is claimed that such services may delay nursing home placement. 4 , 7 9 A recent Norwegian study found higher self-reported quality of life among people with dementia attending day care services compared to those not receiving day care. 10 By 2020, all Norwegian municipalities will be obliged to offer day care to people with dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Day care for older people can be defined in different ways; a 'social model' where centres aim to provide socialisation and activities and a 'medical model' where health services and rehabilitation are provided (5). Overall, people with dementia who attend day care services typically express high degrees of satisfaction (6)(7)(8). Attending a day care centre provides the opportunity for social interaction and a sense of structure and routine (9,10), and day care has been shown to provide people with dementia with a range of benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Attending a day care centre provides the opportunity for social interaction and a sense of structure and routine (9,10), and day care has been shown to provide people with dementia with a range of benefits. These include: increased wellbeing (7,11); better sleeping habits (11,12); reduced neuropsychiatric symptoms and use of psychotropic drugs (12,13); and, reduced family carer stress (14,15). Having access to day care can also improve the relationship between the carer and the person with dementia by providing time apart and facilitating employment (5).…”
Section: Introductionmentioning
confidence: 99%